Pengukuran Kualitas Layanan Website Reglab Informatika Menggunakan Metode Webqual 4.0 - Hadi, Wisnu Setiawan; Umar, Rusydi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Reglab.tif.uad.ac.id is a website used as an information media in the informatics study program for practical purposes. There are several complaints from students about the reglab website, including the language is still mixed between Indonesian and English, the appearance of the website still has some images that do not load and the chat feature on the website does not exist. Based on these problems, a measurement of the quality of the reglab website service will be carried out using the webqual 4.0 method. The results of the webqual 4.0 measurement, namely the webqual 4.0 dimensions, partially or simultaneously show the relationship between the webqual dimensions, namely the usability dimension, information quality, and service interaction quality, which affect the user satisfaction dimension. Recommendations given to website developers are based on the lowest value of each webqual 4.0 dimension. From the usability dimension, the recommendation is to add reference links or books that according to the lecturers can help practicums. From the information quality dimension, it is an improvement in the appropriate format such as language. From the quality of service interaction, it is providing interactive chat or question and answer facilities to support the relationship between website users and the regla party. From the dimension of user satisfaction, when carrying out activities on the Reglab website, the speed of accessing the website is slow, then the developer can reduce the number of plugins used, programs and images can be optimized so that the website can be lighter when accessed, update the programming language used and carry out regular maintenance to check the website.